A Comparison of Pentosan Polysulphate (SP54) and Heparin I: Mechanism of Action on Blood Coagulation - Fischer, A-M; Barrowcliffe, T W; Thomas, D P (Thrombosis and Haemostasis, 1982)
The effects of SP54 on inhibition of thrombin, factor Xa and factor IXa, in the presence and absence of antithrombin III (At III), have been examined and compared to those of heparin. SP54 potentiated inhibition of thrombin and Xa by purified At III, but crossed immunoelectrophoresis data indicated that these effects were mediated by binding to the enzyme, rather than to At III. Relatively high concentrations of SP54 were required for inhibition of thrombin and Xa in plasma, but at concentrations less than 2 μg/ml there was a marked suppression of the intrinsic activation of factor X. This effect was shown to be independent of At III, and to be due largely to inhibition of factor IXa. Prothrombin activation by factor Xa and phospholipid was also suppressed by SP54 in the absence of At III, and its effect on the APTT was also shown to be independent of At III. It is concluded that at relatively low concentrations the anticoagulant actions of SP54 are mainly due to these At III-independent pathways.
Keywords: Heparin; Pentosan polysulphate; SP54; Mechanism in vitro